(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
The article gives the concept of public power, examines the system of public power at all levels of its implementation, pays attention to the specifics of the organization and implementation of public power in modern Russia. The law on the amendment to the Constitution of the Russian Federation of March 14, 2020 No. 1-FKZ "On improving the regulation of certain issues of the organization and functioning of public power" has actualized the issues of modernizing the system of power in modern Russia, determined the further development of scientific research in this area. The new provisions of the organization and functioning of public authorities need to be comprehended from the point of view of the implementation of the principles of separation, unity and interaction of authorities, observance of the starting principles of the federal structure and democratic procedures, ensuring the supremacy of human and civil rights and freedoms. The authors point out that the search for a balance between the legislative and executive branches of government, as well as issues of improving the legal framework for organizing power in the constituent entities of the federation, including the implementation of control functions, remains an urgent problem for the Russian system of public power.